Lower and Middle Paleolithic sites from the Rufa Graben, central Saudi Arabia - Crassard, Rémy; Hilbert, Yamandu H. (Proceedings of the Seminar for Arabian Studies, 2020)
The Arabian Peninsula sits at a crucial location along either purposed pathways of Pleistocene human dispersals from North Africa to Eurasia and has an unexpected archaeological richness found across what are now deserts, mountains, plateaus, ancient lake basins, and dry rivers. Starting in 2011 and continuing in 2013 and 2015, surveys and excavation activities conducted by an international team of scientists have mapped traces of the first humans in the Rufa Graben, close to the modern town of Al-Kharj. The survey has revealed forty-seven sites and data on 1685 stone tools (lithics) from Lower and Middle Palaeolithic assemblages. Here the results of the technological and typological investigation of the Lower and Middle Palaeolithic artefacts from Rufa Graben sites are presented. Lower Palaeolithic artefacts, mostly ovoid and amygdaloid hand-axes, have been found on slopes and valleys along the hills. Based on the presence of Levallois cores, the majority of sites were attributed to the Arabian Middle Palaeolithic. Together these sites show a specific trend where raw material outcrops located in the valleys tend to show the highest amount of internal variability in terms of size, weathering, core reduction strategy, and possible chronology. Sites located in high areas, such as hill crests, terraces, and slopes present homogeneous use of core technology; as in most cases they are not on a quartzite outcrop, they are more likely to be the result of short knapping events.